The Effect Of Health Education On Improving Parents 'Knowledge About Diarrhea Management In Children - Nadia Alfira; Fatmawati; Nurhasanah (Jurnal Life Birth, 2019)
Diarrhea is almost one in five child deaths caused by diarrhea in developing countries. Based on data obtained from the medical records of Sinjai Regional Hospital in 2016 the number of diarrhea patients in children was 195 cases (43%), in 2017 there were 117 cases (26%), and in 2018 the number of diarrhea patients was 136 cases (30%). One of the causes of the increasing incidence of diarrhea is the low level of parental knowledge about diarrhea management, so it is necessary to increase the knowledge of parents in diarrhea management. This study aims to determine the "Influence of Health Education on Increasing Parental Knowledge about Diarrhea Management in Children in the Sinjai Regional Children's Hospital in 2019. The study was conducted with a Pre-Experimental method with the design of the One Group Pre-Post-Test, the population consisted of 136 people. The sampling technique used was consecutive sampling with a sample of 37 parents of children, with a questionnaire instrument that was carried out for one month. The test used in this study is a paired T-test to find out the difference between before and after health education in diarrhea management. Based on data analysis, it is known that the level of knowledge of children's parents before being given health education, 15 respondents (40.5%) were in the lack of knowledge category, whereas after being given health education 34 respondents (91.9%) in the good knowledge category increased. This study shows the parents of children who get health education affect the increase in parental knowledge about diarrhea management in children and can contribute ideas in broadening the insights of concepts, theories, and knowledge and can be used as a reference in conducting further research.